When you multiply a base with an exponent by a base with an exponent, you add the exponents together. (But you can only combine the exponents when the bases are the same)
For example:
(can't combine the exponents because they have different bases of x and y)
![x^1(x^2)=x^((1+2))=x^3](https://img.qammunity.org/2021/formulas/mathematics/college/1wpchz56sjiy4ofd4h5s381jkg56tge3z0.png)
![2^2(2^2)=2^((2+2))=2^4=16](https://img.qammunity.org/2021/formulas/mathematics/college/ytcynq5xxdmzbpvhpfzebqq0y47xi7knkb.png)
Your answer is C